Exploring the relationship between teacher growth mindset, grit, mindfulness, and EFL teachers’ well-being - He, Jianyu; Iskhar, Shisir; Yang, Yan; Aisuluu, Moldobaeva (Frontiers in Psychology, 2023)
Introduction This study examines the relationship between teacher growth mindset, mindfulness, grit, and teacher well-being, with a particular emphasis on the mediating role of grit. Methods The study involved 547 Chinese EFL teachers as participants. Data collection utilized validated measures of growth mindset, mindfulness, grit, and occupational well-being. Structural equation modeling was employed to analyze the data and investigate the proposed relationships. Results The findings reveal several important relationships. Firstly, both teacher growth mindset and teacher grit exhibit a direct positive influence on teacher well-being. Secondly, teacher grit acts as a mediator in the connection between teacher mindfulness and teacher occupational well-being. This suggests that the positive impact of mindfulness on well-being is, in part, explained by the presence of grit. Discussion These findings significantly contribute to our comprehension of the factors influencing teacher well-being. They underscore the importance of cultivating growth mindset, mindfulness, and grit in educational contexts. Moreover, the implications of these findings for teacher training and support programs are discussed.